Usaha Pencegahan Pencemaran Pada Industri Penyamakan Kulit - Robiatun Robiatun (Jurnal Kimia dan Kemasan, 2001)
Leather industries produce a complicated pollution. Action to minimize the pollution it had been done in the leather industry which is middle industry. To implement this programme will save 50 % of fresh water in hide washing process (batch system) compared to continuous processed, while install screen in wastewater 's flaw will reduce solid waste in the sedimentation tank. Recycling the de!iming washing water for washing the raw hide hes no effect to leather quality (remain unchange). While recycling pickle washing water added with tanning washing water for tanning process will produce pollutant which chrome oxide in it is 50 % less than as usually and the wet blue product is still fulfil the standard requirement. By experiment recycling pickle-washing water added with chrome oxide for tanning process has no effect to the finished leather qual